Qualitative Inquiry on Marketing Strategies for Promotion of Library Services in University Libraries in Nigeria - Zubair, Muhammad Salihu; Mamat, Wan Ali Wan; Noor, Noor Hasrul Nizan Mohammad (2017)
The paper aims to examine the situation of information service marketing in university libraries in Nigeria. It focuses on understanding how the university libraries adopt and implement the marketing strategies to promote their services to current and potential users. It also finds out the factors that motivate the libraries to market their services to user community. The 7P’s of service marketing mix model was used by the researchers to examine the marketing strategies adopted and implemented by the university libraries to market their services to potential users. This study adopts qualitative research method using semi structured interview instrument for collecting data from six (6) librarians across the selected six federal university libraries in six geopolitical zones of Nigeria. The qualitative data was analysed thematically based on the research questions. The disproportionate stratified sampling technique was used to select the universities and the purposive sampling technique was employed to sample the librarians. The findings revealed that the university libraries adopted and implemented the marketing strategies for creating awareness of library services, improving services and building relationships with user segments of students, academics and administrative staff. The marketing strategies implemented by the libraries include product, promotion, place, people, process and physical evidence strategies excluding pricing strategy. This study is useful and helpful to academic libraries in marketing of their services by implementing the service marketing strategies. The findings are useful to improve the understanding of librarians on relevance and application of marketing mix model in marketing library services. This study contributes to the growing body of knowledge on the implementation of service marketing mix in university libraries as non-profit making and service organizations. The strategies enable the libraries to get users involved in the life of library activities.